Genetic studies on Jatropha Plant (Jatropha Curcas Lam) using diferent Gamma Radiation doses - Sharkh AY - Abo Remalia S.I.H - Abou El Enin MM - Nabil A, (Arab Journal for Sciences and Research Publishing, 2015)
The study aimed to compare, the effects of different doses of gamma radiation on germination survival percentage and growth of Jatropha plant, the seeds were treated with three doses of gamma radiation (5, 10 and 15 kr) and arranged in a randomized complete block design with three replications. The results showed significant differences among the three doses for seed germination after 7, 14 and 21 days from sowing in vitroand invivo experiments and on the other handplant height andno. of Leaves /plantwere recorded after 10,20, 30,100,120 and 130 days from sowing invivo experiments andthe low dose 5 kr seemed to have a stimulating effect on these traits, on the other hand the high dose 15 kr caused significant reduction as compared to the control for all studied traits.
Keywords: Jatropha callus; gamma radiation; seed germination